SOURCES FOR THE STUDY OF THE TRADITIONAL CULTURE OF THE PEOPLES OF KABARDINO-BALKARIA, KARACHAY-CHERKESSIA AND ADYGEA IN THE EARLY 20TH CENTURY - Barazbiev, Muslim Ismailovic; Murzahanov, Urij Isaevic (History, Archeology and Ethnography of the Caucasus, 2019)
The current stage of the development of caucasiology is the result of the work of professional scholars (archaeologists, anthropologists, ethnographers, historians, philologists) and local historians who studied the North Caucasus, identified, accumulated and analyzed the source base, formed historical knowledge about the region. The active work of scientific communities and institutes, both metropolitan and North-Caucasian ones, private individuals and amateurs of antiquity in recognizing, collecting, researching and introducing the sources of the pre-revolutionary period has defined an organic inclusion of the North-Caucasus in the common socio-cultural space of the country, facilitated the establishment of inter-ethnic dialogue and mutual understanding of the peoples of the Caucasus and Russia.The purpose of this article is to consider various groups of historical sources of the early 20th century, from which the readers could draw information of interest to it about the traditional culture of the peoples of Kabardino-Balkaria, Karachay-Cherkessia and Adygea. These include bibliographic indexes (I.I. Dmitrienko, V.N. Kharuzina, E.I. Yakushkin, D.K. Zelenin, D.D. Pagirev, E.D. Felitsyn, V.D. Shamray, I .M. Pulner, etc.); ongoing publications ("Kavkazsky kalendar", "Collection of materials for describing the lands and tribes of the Caucasus", "Collection of information about Caucasian highlanders", etc.); periodicals (“Tersky Vedomosti” (Vladikavkaz), “Terek” (Vladikavkaz), “Caucasus” (Tiflis), “Kazbek” (Vladikavkaz), “Novoe Obozrenie” (Tiflis), “Severny Kavkaz” (Stavropol), “Kubanskie Regionalnie Vedomosti” (Ekaterinodar); local history materials published by intellectual communities; papers and essays by caucasiologists, representatives of the Russian intelligentsia; reference books and guides, etc.The relevance of the work lies in the need for a critical analysis of existing historical sources, since sources on traditional culture occupy a special place in historical research, and it is traditional culture that reflects the ethnocultural strata of different eras, being a kind of historical image of the people.
Keywords: Ethnography; traditional culture; bibliographies; scientific society; AIRGO; periodic and continuing publications; historiography.